Longitudinal effects of basic psychological need support on the development of intrinsic motivation and perceived competence in physical education. A multilevel study - Kruse, Felix; Büchel, Sonja; Brühwiler, Christian (Frontiers in Psychology, 2024)
Background: Grounded in self-determination theory, this article deals with a multidimensional measurement of the support of the basic psychological needs and the individual and combined effects on the development of intrinsic motivation and perceived competence in physical education. In addition to autonomy support, competence support and relatedness support, peer relatedness support is examined as an additional factor. Methods: A total of 1047 students from 72 classes in Switzerland took part in the study. The hypothesized four factorial structure was analyzed using multilevel confirmatory factor analyses. Longitudinal measurement invariance testing of intrinsic motivation and perceived competence indicates scalar measurement invariance. Multilevel regression analyses were specified to analysis the longitudinal effects on the development of intrinsic motivation and perceived competence. Results: Results of multilevel confirmatory factor analysis indicate that the hypothesized four-factor model is to be favored over alternative models at both levels. Regarding the prediction of the development of intrinsic motivation and perceived competence our study underlines the predictive value of basic psychological need support. The models that examine the effects of the individual predictors indicate that the effects are largely consistent with expectations at both the class and individual level. At class level, however, autonomy support appears to be no significant predictor for the development of intrinsic motivation, but for perceived competence. Peer relatedness support is a significant predictor for both outcome variables at both levels of analysis. Regarding the simultaneous integration of all predictors, only the effects of peer relatedness support remain significant for both outcome variables. Discussion: The empirical support of the multidimensionality of the instrument is particularly interesting in the context of the common conceptualization of a unidimensional measurement of autonomy support or a composite factor of psychological need support, whereby only few studies have adequately tested the factorial validity. Although significant effects of supportive teacher behaviors can be demonstrated in the multilevel regression analyses, it is also indicated that the different dimensions lack of incremental predictive validity. Particularly noteworthy is the rarely investigated role of peer relatedness support, which has been shown to be a meaningful predictor, even when supportive teacher behaviors are taken into account.